Unveiling Global Trends in Coronary Heart Disease Research: A Scopus Bibliometric Analysis - Qonita Sari Bustomi; Salma Fathinah; Nurul Ilma Haryono; Rian Ka Praja (PT Syamilah Literasi Islami, 2024)
The heart stands as a critical organ within the human body, susceptible to various disorders with distinct characteristics. Notably, coronary heart disease, due to its escalating worldwide prevalence, commands significant attention. However, this disease is not restricted to a specific age group and can afflict those not adhering to healthy lifestyles. In this study, our objective is to investigate the global epidemiology of coronary heart disease from 2014 to 2023 by conducting a comprehensive bibliometric analysis of the scientific literature. This study employs Data Collection, Data preprocessing, Co-occurrence Analysis, Co-authorship Analysis, Data Visualization and Analysis, and Ethical Consideration. The data were collected from the Scopus database and filtered by adding the keywords